2018
DOI: 10.1159/000494695
|View full text |Cite
|
Sign up to set email alerts
|

Dandy-Walker Malformation-Like Condition Revealed by Refractory Schizophrenia: A Case Report and Literature Review

Abstract: Introduction: Dandy-Walker malformation is a rare congenital malformation involving cystic dilatation of the fourth ventricle, enlarged posterior fossa, complete or partial agenesis of the cerebellar vermis, elevated tentorium cerebelli, and hydrocephalus. Previous research highlighted a possible role for the cerebellum in schizophrenia as well as the contribution of underlying brain malformations to treatment resistance. Here, we present a case of a Dandy-Walker malformation-like condition revealed by a refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 85 publications
1
21
0
Order By: Relevance
“…Previous case reports have mentioned that there may be a relationship between MCM and psychiatric symptoms. This relationship is more evident in malformations affecting the vermis and cerebellar hemispheres [14,15]. However, in proton magnetic resonance spectroscopy, it was observed that the levels of gamma-aminobutyric acid (GABA) were decreased in the cerebellar tissue of patients diagnosed with unipolar and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports have mentioned that there may be a relationship between MCM and psychiatric symptoms. This relationship is more evident in malformations affecting the vermis and cerebellar hemispheres [14,15]. However, in proton magnetic resonance spectroscopy, it was observed that the levels of gamma-aminobutyric acid (GABA) were decreased in the cerebellar tissue of patients diagnosed with unipolar and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…DWM is a part of a rare neurodevelopmental diseases called Dandy-Walker Complex [10] . It is characterized by an enlargement of the posterior fossa, cystic dilatation of the fourth ventricle, agenesis (partial or complete) of the cerebellar vermis [11] .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of pathologies have been implicated. A literature search in PubMed database revealed 21 studies associating Dandy Walker Complex involving the cerebellum with psychotic features [ 8 , 9 ]. Associations between cerebellar stroke and psychosis have also been revealed in two recently published case reports [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%